(untitled) (The Review of Diabetic Studies, 2025)
Breast cancer patients undergoing paclitaxel (Taxol) chemotherapy frequently develop paclitaxel-induced a peripheral neuropathy (PIPN), a toxicity that can be considered dose-limiting that significantly impacts quality of life. While the molecular mechanisms remain incompletely understood, emerging evidence suggests that NLRP3 inflammasome activation may play key roles in PIPN pathogenesis. Objective: This study explored the connection between NLRP3 inflammasome activation, pro-inflammatory cytokine levels, and the emergence of PIPN in Iraqi patients with breast cancer (BC) receiving Taxol chemotherapy. Methods: Blood sample draw done and distributed into two tubes: Trizol containing tube for evaluation the gene expression of NLRP3 gene by qRT-PCR and gel tube for measurement of interleukin level Results: We observed significant molecular changes associated with neurotoxicity. IL-1β levels nearly doubled from 9.43±1.33 pg/mL at baseline to 17.66±3.62 pg/mL post-treatment (p<0.05), while IL-18 showed a modest but consistent increase from 7.16±1.44 pg/mL to 7.30±1.40 pg/mL. Molecular analysis revealed enhanced NLRP3 inflammasome activity, as evidenced by folding expression of NLRP3 was up regulated in BC patients after treatment by (5.4) times than before treatment (3.16). Conclusions: This study examined the relationship between the expression of the NLRP3 gene and pro-inflammatory cytokines (IL-1β and IL-18), and the Onset of PIPN in Iraqi BC patients post treatment with Taxol (paclitaxel).The results showed that these biomarkers changed significantly after treatment, which may indicate that they play a part in the pathophysiology of PIPN